Effect Of Firms Attributes On Non-Performing Loans Of Listed Deposit Money Banks In Nigeria - Mohammed Jibril (HM Journals, 2021)
This study investigates the effect of firm’s attributes on non-performing loans of listeddeposit money banks in Nigeria. Firm attributes was proxied by (firms size, liquidity andcapital adequacy) while non-performing loans was proxied by (the ratio of non-performingloans to total loan). 2010-2019 were the period under review. The study adopts the ex-postfactoresearch design. Annual data used in the study were sourced from the fact books ofthe Nigerian stock exchange and the financial statement of the banks. Descriptivestatistics, correlation matrix and the ordinary least square (OLS) multiple regressiontechniques were the main statistical tools used in the analysis of data. Additionally, thestudy conducted hausman test to choose between the fixed and random effect model whichwill be acceptable. The anticipated income theory was relied on as it provides the mostuseful theoretical explanation for the study. The result of the regression reveals that, firmsize and liquidity has no significant effect of non-performing loan, while capital adequacyhas significant effect on non-performing loans. Based on the findings, the study concludesthat the CBN should raise capital adequacy ratio from10% since increasing CAR reducesNPLs base on the findings of this study. Banks should also sure up their capital basedbecause it serve as a buffer and it will enables them absorb the challenges that may arisefrom the volume of non-performing loan they may encounter..